Relationship of Posterior Capsular Opacification and Capsular Bend Type Investigation Based on Swept-source Optical Coherence Tomography. (2nd January 2020) - Fang, Yu; Xixia, Ding; Jin, Li; Lei, Lin; Pingjun, Chang; Hongfang, Zhang; Yun-e, Zhao
ABSTRACT: Purpose: To investigate the relationship between capsular bend type and posterior capsule opacification (PCO) at a three-dimensional (3D) level using high-speed swept-source optical coherence tomography (SS-OCT). Methods: This was a retrospective study. A total of 99 eyes that underwent standard cataract surgery with phacoemulsification 2 years ago were analyzed. Standard SS-OCT radial scanning was performed in all eyes and the obtained photos were used for morphological observations of the capsular bend-IOL complex, the adhesion of posterior capsule to the IOL optic, and the position of the anterior capsulorhexis. Digital retroillumination photographs were taken of the posterior capsule of each eye to evaluate PCO (scoring and area). Results: In terms of the PCO score and area, there was no statistical difference between eyes with complete and incomplete adhesion of posterior capsule to IOL (both P > .05), whereas the partial overlap group showed a statistical difference greater than the total overlap group ( P < .05). There were two types of capsular bends, completed adhesion (CA) and incomplete adhesion (IA). IA was divided into funnel adhesion (IA-F), parallel adhesion (IA-P), and detached adhesion (IA-D). The incomplete adhesion index (IAI) varied between eyes and ranged from 0 to 1. The PCO score and area in the high IAI group (higher than 0.50) were significantly greater than the low IAI group (< 0.50) ( P < .05). In addition, the PCO score and area were significantly higher in the cohort with at least one IA-D capsular bend in six districts to the group that did not have IA-D capsular bend ( P < .05). Conclusions: Complete or incomplete adhesion of the posterior capsule to the IOL optic may not be necessary for the development of PCO. Our study suggests that capsular bend type may be used as an index to predict PCO.